Il crocifisso davanti alle Sezioni Unite della Cassazione: difesa di diritti o accanimento iconoclasta? (Stato, Chiese e pluralismo confessionale, 2021)
1 - Con ordinanza n. 19618 del 18 settembre 2020 una sezione della Cassazione ha rimesso alle Sezioni Unite la decisione di un ricorso contro la sentenza della Corte d’appello di Perugia, che ha respinto l’appello proposto da un docente contro la sentenza del Tribunale della stessa sede che aveva ritenuto legittima la sanzione disciplinare della temporanea sospensione dall’insegnamento comminatagli dall’Ufficio Scolastico Provinciale. Alla base di tale provvedimento vi era stato il comportamento del docente, il quale - secondo quanto esposto nell’ordinanza in oggetto - (segue)The Crucifix controversy before the Supreme Court’s United Sections: protection of rights or iconoclast fury?ABSTRACT: This short paper critically examines, in the light of Italian and European case-law, the contents and juridical arguments of an order issued by a Section of the Italian Court of Cassation, which remits to the United Sections – the highest level of the Court – the decision on the Crucifix controversy arisen in a State school. Differently from previuos cases, in the presento one the teacher, and not the students or their families, removed the crucifix, hanging on the wall of the classroom as required by an old regulation, against student’s will. This repeated behaviour stirred a controversy between the teacher and the school director, which is now under judgment. Under the Italian law, secularism is not in contrast with the display of religious symbols in a State school, whose mission is that of fostering and promoting the development of children’s and student’s personality also through the free exchange of different ideas and points of view.